In situ detection of lipid peroxidation in chronic hepatitis C: correlation with pathological features. Issue 5 (May 1997) - Paradis, V; Mathurin, P; Kollinger, M; Imbert-Bismut, F; Charlotte, F; Piton, A; Opolon, P; Holstege, A; Poynard, T; Bedossa, P
Abstract : AIMS: To assess the occurrence of lipid peroxidation in chronic hepatitis C and to evaluate its relation to pathological features and liver iron concentrations. METHODS: Liver biopsy samples of 43 patients with untreated chronic hepatitis C were studied by immunohistochemistry using specific antibodies directed against two major aldehyde metabolites of lipid peroxidation, malondialdehyde (MDA), and 4-hydroxynonenal (HNE). RESULTS: MDA and HNE adducts (aldehydes covalently linked to another molecule) were detected in the liver samples in 77% and 30% of cases, respectively. MDA adducts were detected both in the extracellular matrix and sinusoidal cells localised in areas of periportal and lobular necrosis. HNE adducts appeared in the cytoplasm of only a few hepatocytes. Comparison of the semiquantitative assessment of adducts (MDA and HNE indexes) with the grading and the staging of chronic hepatitis showed that the MDA index was correlated with fibrosis score (p < 0.001) and the grade of activity (p < 0.01). There was also a tendency to correlation with liver iron concentration (p = 0.09). No correlation was observed between the HNE index and pathological features or liver iron concentration. CONCLUSION: Lipid peroxidation products are detectable in the liver of chronic hepatitis C patients. The presence of MDA adducts in areas of active fibrogenesis and the correlation between the MDA index and fibrosis score suggest a role for lipid peroxidation in liver fibrosis.